Post mission trajectory smoothing for the Isurus AUV - Aníbal Matos (2003)
In this paper we describe an algorithm that produces a post mission estimate of the spatial evolution of the Isurus AUV. To make this post processing possible, the navigation system records on the vehicle logging system all the navigation data received during the mission execution. The data comprise the depth of the vehicle, the outputs of the tilt sensors and digital compass, the angular velocity of the propeller, as well as acoustic range measurements to a set of transponders. After mission completion, the logged data is then processed to produce the estimate of the evolution of the vehicle. The algorithm used to process this data is based on a fixed interval nonlinear stochastic smoothing scheme and produces an estimate that evolves continuously in time. For each instant of time, the post mission position estimate is based on all the information collected during the mission, as opposed to real time estimates that can only take into account past data.